Unique Glass from Finland. - Kahma, Marketta (Helsinki : Libris Oy, 1984)
Franck, Kaj ; Kallio, Heikki ; Nurminen, Kertu ; Merikallio, Mikko ; Sarpaneva, Timo ; Orvola, Heikki ; Toikka, Inkeri ; Toikka, Oiva ; et al.
kunstcatalogus
Keywords: Finland